Knowledge, attitudes and practices regarding dengue, chikungunya, and zika and their vector Aedes aegypti in Villavicencio, Colombia (2023)
Background: Aedes aegypti transmits dengue, chikungunya and zika, and high infestation rates of this mosquito are responsible for maintaining these arbovirus outbreaks in endemic areas Objective: To estimate the knowledge, attitudes, and practices regarding dengue, chikungunya, and zika and their vector Aedes aegypti in Villavicencio, Colombia. Methods: A descriptive, cross-sectional study was conducted. Verbal informed consent was obtained from adults and then interviewed using a structured questionnaire. Houses were randomly selected; in the event that no one was home, the next house was selected. Entomological data were recorded to calculate the larval indexes at homes. Results: Seventy-six houses (309 people) were evaluated. 70% of subjects were aware that dengue, chikungunya or zika are viral diseases. Fever was considered the most important symptom and could be related to the experience of having these diseases at home. 79.45% knew that a mosquito transmits these diseases but did not know the scientific name or that only the female bites. 81.36% did not know the life cycle of the mosquito but were aware that the elimination of breeding sites and destruction of containers with water could aid in transmission prevention. 88.46% recognized that the community should be responsible for these control actions at home, but the recommendations are not implemented due to the lack of interest or apathy. The average house index was 40.3%, and Breteau index was 47.66%. Low tanks represented the most common breeding site. Conclusion: It is necessary to review campaigns, communication, and education promoted in the municipality because they do not reflect the knowledge of the people. © 2017 Jaramillo Ramírez and Álvarez.